A cure for the common company a well-being prescription for a happier, healthier, and more resilient workforce - Safeer, Richard (Wiley, 2023)
The author have assessed cultures, trained leaders, and conducted and explored research on the intersection of individual and organizational behavior. In his work, what he hears again and again is that leaders genuinely care about the people on their teams: they want them to have lower stress levels, they want them to feel healthy and happy, and they want them to be excited to come to work! But they don?t know how to make that happen. Culture is complicated and culture change is not something you necessarily learn in business school or when you?re promoted to a leadership position. It?s especially hard when it comes to health. It?s a challenging and potentially uncomfortable topic, and leaders may project their own experiences onto others, which gets the organization and the culture into trouble. Leaders need help in their efforts to help employees, and that is the practical promise of this book. The missing piece is a method and framework for influencing and shaping a culture of health. It?s the heart of the work the authors do, and this book will give readers the knowledge and tools to do the same"--